Problems with Online Criminal Justice in Criminal Procedure Law Due to the Covid-19 Pandemic - Ida Bagus Gde Subawa (Universitas Pendidikan Ganesha, 2021)
The world is in crisis due to the Covid-19 pandemic. Corona Virus Disease 2019 (Covid-19) is a disease that was first discovered in the city of Wuhan, China. The transmission of Covid-19 in the People's Republic of China (PRC) occurred in 2019 and caused the death of Chinese citizens. By early 2020, the spread had spread to every country, including Indonesia. The wide spread of Covid-19 throughout Indonesia has resulted in the government declaring a health emergency and implementing a lockdown policy by limiting activities that trigger the massive spread of the Covid-19 virus. Activities that were initially carried out offline must be carried out online, and one of these activities is court proceedings. Due to the Covid-19 pandemic, every activity, including the judiciary, is carried out online. This study aims to examine the problems that occur as a result of the implementation of online criminal justice in criminal procedural law. This research is descriptive research with a literature study method. The results of the study show that the implementation of online trials creates problems that are considered inconsistent with several principles and contrary to the Criminal Procedure Code, some of which are the validity of evidence in court, then there is an examination of the defendant in court until the last one is the personnel and equipment. which is not supported. Another problem is the Regulation of the Supreme Court of the Republic of Indonesia No. 4 of 2020 concerning the Administration and Trial of Criminal Cases in Courts Electronically which is contrary to the principles of Courts Open to the Public and Quick Trials.